Hambatan Struktural Konflik Adat Terhadap Keadilan Sosial-Ekologis Generasi Emas - Sabila, Najwa; Kusumawati, Retno; Jayatri, Serly Nurharis; Fazrina, Indira Nazwa; Yuliani, Shahibah (Universitas Jabal Ghafur, 2025)
Indonesia's Golden Generation 2045 is the nation's vision to create superior and globally competitive human resources in a just and sustainable society. This study aims to describe the structural barriers of customary conflicts to the socio-ecological justice of the golden generation in the form of how inequality in land ownership, cultural identity crisis, and marginalization of customary rights hinder the Sustainable Development Goals (SDGs), especially in eradicating poverty (SDGs 1), reducing inequality (SDGs 10), maintaining terrestrial ecosystems (SDGs 15), and peace, justice, and strong institutions (SDGs 16). Through a systematic literature review, it was found that state and corporate domination of customary land, weak legal recognition, and exclusive development policies exacerbate the conflict. Case studies in Java show serious impacts on indigenous youth, including loss of access to education and resources. This study emphasizes the urgency of resolving customary conflicts to realize equitable sustainable development.Keywords : Indigenous conflict, Golden Generation, SDGs, Socio-ecological justice